MENINGKATKAN PENGUASAAN MENELADANI KHALIHAF ABU BAKAR DAN UMAR MENGGUNAKAN TEKNIK BERCERITA MELALUI TUTOR SEBAYA PADA SISWA KELAS VI SDN 005 BONTANG - Zaitun Zaitun (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2016)
This study is aimed at increasing mastery on the history of teaching values of Abu Bakar and Umar Bin Khattab, the emperor after Nabi Muhammad.  The study uses classroom action research as the design to implement the same age tutor through story telling techniques.  Using two cycles, this study assignes teh sixth grade students of SDN 005 Botang as research subject.  This study discovers that learning actuivities increase and the average score increases from 6,5 to 8.2.  The participations and involvements during the learning process also increase so that the study is finished in the second cycle.  This study proves that using the same-age tutor to teach haracters of Abu Bakar and Umar as kulafaur rasyidin is favorable.